2012
DOI: 10.1136/sextrans-2012-050491
|View full text |Cite
|
Sign up to set email alerts
|

Systematic review examining differences in HIV, sexually transmitted infections and health-related harms between migrant and non-migrant female sex workers

Abstract: The lack of consistent differences in risk between migrants and non-migrants highlights the importance of the local context in mediating risk among migrant FSWs. The higher prevalence of HIV among some FSWs originating from African countries is likely to be due to infection at home where HIV prevalence is high. There is a need for ongoing monitoring and research to understand the nature of risk among migrants, how it differs from that of local FSWs and changes over time to inform the delivery of services.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
101
1
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 79 publications
(109 citation statements)
references
References 51 publications
(172 reference statements)
6
101
1
1
Order By: Relevance
“…While the main focus of the review is HIV vulnerability, PWID in Europe are also vulnerable to hepatitis C virus (HCV) [51]. Reviewed studies show HCV prevalence estimates between 52% and 94% among PWID in the West, 37% and 74% in Central Europe, and between 54% and 96% in the East.…”
Section: Hcv Infectionmentioning
confidence: 99%
See 4 more Smart Citations
“…While the main focus of the review is HIV vulnerability, PWID in Europe are also vulnerable to hepatitis C virus (HCV) [51]. Reviewed studies show HCV prevalence estimates between 52% and 94% among PWID in the West, 37% and 74% in Central Europe, and between 54% and 96% in the East.…”
Section: Hcv Infectionmentioning
confidence: 99%
“…Data from Europe show that levels of sexual and physical violence among SWs were universally high, particularly among minority groups such as Roma populations and transvestites [47,50]. Qualitative data from Western Europe suggest that violence among SWs is ubiquitous and compounded by drug use and the stigma associated with sex work [25,26,51]. Violence was the most frequently reported risk associated with work by respondents of the TAMPEP study who reported violence from clients, robberies, and verbal abuse from the police.…”
Section: Violencementioning
confidence: 99%
See 3 more Smart Citations